Dampak Covid-19 Terhadap Pelaksanaan Pekerjaan Konstruksi Multi Years - Hafnidar A Rani; Widya Soviana; Rahimi A. Rahman (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2022)
The Covid-19 has impacted all human aspects. One of the impacts is the construction sector for infrastructure construction become an important component supporting national economic development. The problem of the study was whether the quality, cost and time factors of multi-year construction project work implementation is influenced by the Covid-19 pandemic. The study aimed to find out how much Covid-19 pandemic influencing the quality, cost and time of multi-year construction projects implementation. The study methods used are a quantitative approach method by using Guttman scale questionnaire instrument and qualitative approach method by using interviews. The sampling technique used is quota sampling from project implementing elements consisting of project owners, contractors and construction management consultants on construction and revitalization project of Balohan Port. The study case selection because the project was indicated impacted by Covid-19 pandemic. Regression analysis resulted that if there is no change to the quality, cost and time variables, the impact of the Covid-19 pandemic on the multi-year projects implementation was 0.855 units. Based on the R square value, the impact of the Covid-19 pandemic on multi-year projects was influenced by the quality, cost and time variables as 65% ​​while 35% is influenced by other factors. The quality of multi-year projects was affected by disruption of project implementation activities, the cost was affected by additional costs due to health protocols and the delays was affected by waiting time because of due to materials scarcity arrived in the project site. It is concluded that the quality, cost and time variables impact Covid-19 pandemic in which the cost factor become the most affected to the implementation of multi-year projects as 74.50% as mean percentage